Comparison of Experimental Results with Numerical Solution of Thermal Stress Analysis - Zuzana Stankovicova; Vladimir Dekys; Leszek Radziszewski; Milan Uhricik; Milan Sapieta (Communications - Scientific letters of the University of Zilina, 2015)
This paper presents experimental measurement of the first stress invariant on the plate with hole at fatigue testing machine due to adiabatic elastic deformation. The theoretical part is concentrated on the theory of thermal stress analysis focusing on thermoelastic analysis. The experimental part is dedicated to the postprocessing of the measured data including analytical and numerical solutions for the plate with hole using finite element method (FEM).